Development and Validation of a Self-Quantification Scale for Patients With Hypertension - Guiyue Ma; Guiyue Ma; Guiyue Ma; Zhuqing Zhong; Zhuqing Zhong; Yinglong Duan; Zhiying Shen; Ning Qin; Dehua Hu (Frontiers Media S.A., 2022)
BackgroundThe self-management ability of patients with hypertension is poor, and self-quantification increases gradually with the development of electronics. Self-quantification for patients with hypertension has important implications for individual health. However, there is a lack of relevant scales at present, and we aim to develop a self-quantified scale for patients with hypertension.MethodsThe instrument was developed based on protection motivation theory with literature review, a qualitative interview study and focus group discussions, and pilot testing. A total of 360 patients with hypertension were investigated using the scale. The psychometric properties of the scale were evaluated concerning validity and reliability employing internal consistency reliability, split-half reliability, test-retest reliability, content validity (S-CVI/Ave and I-CVI), and construct validity (exploratory factor analysis and confirmatory factor analysis).ResultsThe final scale had 30 items with seven sub-domains. The Cronbach's α for all domains was 0.900 with a range of 0.817-0.938. The split-half reliability coefficient for all domains was 0.743 with a range of 0.700-0.888. The test-retest reliability coefficient for all domains was 0.880 with a range of 0.849-0.943. The S-CVI/Ave for all domains was 0.922 with a range of 0.906- 0.950, and the I-CVI of each item was a range of 0.800-1.000. The result of confirmatory factor analysis of this scale showed that χ2/df was 2.499, RMSEA = 0.065, GFI=0.865, NFI=0.894, IFI=0.934, TLI=0.914, CFI=0.933, RFI=0.865. The Pearson's coefficients between the total scale and every domain were ranging from 0.347 to 0.695, and each domain ranged from 0.130 to 0.481.ConclusionThe scale has good validity and reliability and can be used as a self-quantification scale for patients with hypertension.